Asimetri Kekuasaan : Paradoks Manajemen Kolaborasi Pengelolaan Danau Tempe Sulawesi Selatan - Muhammad Said (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2021)
This paper aims to explain the power asymmetry as a paradox in collaborative management (co-management) of natural resources in Lake Tempe, South Sulawesi. This study uses a qualitative research method with an explanative case study approach. Data collection using participatory observation and indepth interviews. The key informants came from elements of local government, big-scale fishermen, traditional fishermen, farmers, traders, and NGOs. The results of the study concluded that the management of Lake Tempe was marked by asymmetry or power imbalances between actors. Big-scale fisherman actors together with the local government control the means of production, dominate the production of policies and determine the main determinants of the management of Lake Tempe compared to traditional (small-scale) fishermen. The asymmetry of power between these actors has an impact on the imbalance in the benefits and value of resource allocation in Lake Tempe. Big Fisherman Actors and Local Governments get more benefits and value from natural resources. Meanwhile, traditional fishermen actors get fewer benefits and value from natural resources. In a certain stage, the traditional fishermen actors experience a process of marginalization.